Treading the Borderline: Play(ing) with Reality on the Post-Soviet Lithuanian Theatre Stage - Staniskyte, Jurgita (Nordic Theatre Studies, 2018)
Duringthesecond decadeof theIndependence, i.e. at thebeginningof thetwenty-first century the increasing number of performances trying to escape the tradition of anti-mimetic representation and to re-engage with reality appeared on the Lithuanian theatre stage. Fragments of everyday reality, ?real?personalities onstage, autobiographic narratives, historic documents, authentic spaces were becoming increasingly popular, allowing some critics to proclaim theeagerly awaited ?return to realism?. However, acloser analysisof thistendency of contemporary Lithuanian theatre can lead one to believe that such performances do not demonstratetheurgeto return to thetraditional notion of realist representation, but rather to playfully flirt with reality and its reception in the fictional world of theatre. In the light of theoretical and practical revisions of the concepts of reality and its representation, young Lithuanian theatrecreatorsarenot somuch interested in truthful representation of reality, but rather in a performative investigation of processes of representation and their effects on audience perception. One might add that while engaging with the codes of reality or ?real? material onstage, contemporary Lithuanian artists try to dismantle the binary opposition between realistic representation and anti-realistic playfulness, which dominated the symbolic mentality of modern Lithuanian theatre. Various forms of playing with reality and fiction on the Lithuanian theatre stage, their underlying principles and wider cultural implications of such games are the object of investigation of this article. A comparative analysis of performances from Lithuania and Estonia will help to highlight the specific character of Lithuanian theatre as well as to define the patterns of playing with reality present on the post-Soviet Lithuanian stage.